2021
DOI: 10.48129/kjs.13181
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of iron oxide nanoparticles from dates, characterization, and investigation of anticarcinogenic and antimicrobial properties

Abstract: Nanomaterial synthesis using natural biological systems, especially plant-based green synthesis has evinced great excitement and interest. In this study, iron oxide nanomaterials were synthesized from three different varieties of date palms obtained from Srivilliputhur, Tamil Nadu, India. The extract of date palms reduced ferric chloride in solution and facilitated the formation of iron oxide nanomaterials. Phytochemical studies of the extracts obtained from all three varieties of date palms indicated the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…The IC 50 value of OBLE@Mg−Zn NPs for MDA‐MB‐231 cancer cell line was found to be 72.12 μg/mL after 48 hours of incubation time. There exist numerous reports in the literature which support our findings [38–39] . The region for cell inhibitory action may be due to the stimulation of reactive oxygen species and also due to the presence of phytochemical [40] .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The IC 50 value of OBLE@Mg−Zn NPs for MDA‐MB‐231 cancer cell line was found to be 72.12 μg/mL after 48 hours of incubation time. There exist numerous reports in the literature which support our findings [38–39] . The region for cell inhibitory action may be due to the stimulation of reactive oxygen species and also due to the presence of phytochemical [40] .…”
Section: Resultssupporting
confidence: 84%
“…There exist numerous reports in the literature which support our findings. [38][39] The region for cell inhibitory action may be due to the stimulation of reactive oxygen species and also due to the presence of phytochemical. [40] Ocimum Basilicum leaves contain various phytochemicals, such as eugenol, saponins, and tannins, which have been found to exhibit anti-cancer properties against breast cancer.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Figure 5 shows the SEM morphologies of CoFe 2 O 4 , CoBi 0.1 Fe 1.9 O 4 , CoLa 0.1 Fe 1.9 O 4 , and CoAl 0.1 Fe 1.9 O 4 . From the SEM image, it can be observed that the particles have an almost homogeneous distribution, and some are in the form of agglomerations [64]. This is evidenced by the SEM images, which show the incorporation of particles located in the nanometer region.…”
mentioning
confidence: 81%